Faktor-Faktor yang Mempengaruhi Kepuasan Konsumen di Kedai Kopi Kota Pangkalpinang, Provinsi Kepulauan Bangka Belitung - Hijami, Muhammad Fikri (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to examine the effects of price, service, payment methods, and products on customer satisfaction at coffee shops in Pangkalpinang City. This research adopts a quantitative approach and employs a non probability sampling method using a convenience sampling technique. The number of respondents in this study was 120 customers who purchased coffee at coffee shops more than twice per month. Structural Equation Modelling Partial Least Squares (SEM-PLS) was used to analyze the data, supported by the SmartPLS 4 application. The results show that price, service quality, and product variables positively and significantly influence customer satisfaction, whereas the payment method variable has no significant effect on customer satisfaction at coffee shops in Pangkalpinang City. This study is expected to provide strategic input for coffee shop business owners in Pangkalpinang City to enhance customer satisfaction by setting suitable coffee prices, implementing professional service standards, and offering appropriate product variety and quality, thereby enabling more optimal use of business resources.